A new species of Ropalidia Guérin-Méneville, 1831 (Hymenoptera: Vespidae: Polistinae) from the southern Western Ghats, India - K.P. Mohammed Shareef; Lambert Kishore; P. Girish Kumar (Journal of Threatened Taxa, 2015)
A new species, Ropalidia narendrani sp. nov. is described from Southern Western Ghats, Kerala, India. The affinities of the new species are also discussed.